2000
DOI: 10.1074/jbc.m002809200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Glutamine and Asparagine Residues of γ-S Crystallin Are Resistant to in Vivo Deamidation

Abstract: It has been hypothesized that resistance to nonenzymatic deamidation of asparagine and glutamine residues may be an important determinant of protein stability in vivo. As a test of this hypothesis, we analyzed the central region of old human lenses, which contain proteins such as ␥-S crystallin that were synthesized during the fetal-embryonic periods of development. Total protein from the fetal-embryonic region of old human lenses was digested with trypsin, followed by resolution of tryptic fragments containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…15,23 One rationale of this study was to resolve a conflict in the literature regarding deamidation of Gln92. Two studies suggested that there was no deamidation of this residue 11,12 ; however, we obtained clear mass spectral evidence that there is significant deamidation at this site (Fig. 1).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…15,23 One rationale of this study was to resolve a conflict in the literature regarding deamidation of Gln92. Two studies suggested that there was no deamidation of this residue 11,12 ; however, we obtained clear mass spectral evidence that there is significant deamidation at this site (Fig. 1).…”
Section: Discussionmentioning
confidence: 72%
“…A probable reason for the difference in the two datasets is that the earlier studies that found no deamidation were based solely on HPLC elution times in the absence of mass spectral data. 11,12 Apparently, this method is subject to interference by coeluting species and is not sufficiently sensitive to detect deamidation. There are a total of nine Gln residues in cS crystallin, yet few 13 appear to undergo significant deamidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gln deamidations over periods of many years in vivo in slow-turnover proteins of long-lived organisms such as human eye lens proteins (22) can be of substantial biological significance. Gln-Gly sequences in sterically unhindered locations of proteins that lack shorter-lived Asn residues also affect the deamidation index.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the tryptic peptide containing Asp 138(143) is deamidated when isolated from human cataractous lens proteins (44), whereas when the corresponding peptide is isolated from the fetal-embryonic region of aged transparent human lenses, it is not deamidated (46). Asp 138(143) is in the region of the domain dimer interface but has a moderate solvent exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%